The microbiome of medicinal plants: diversity and importance for plant growth, quality and health - Köberl, Martina; Schmidt, Ruth; Ramadan, Elshahat M.; Bauer, Rudolf; Berg, Gabriele (Frontiers in Microbiology, 2013)
Past medicinal plant research primarily focused on bioactive phytochemicals, however the focus is currently shifting due to the recognition that a significant number of phytotherapeutic compounds are actually produced by associated microbes or through interaction with their host. Medicinal plants provide an enormous bioresource of potential use in modern medicine and agriculture, yet their microbiome is largely unknown. The objective of this review is i) to introduce novel insights into the plant microbiome with a focus on medicinal plants, ii) to provide details about plant- and microbe-derived ingredients of medicinal plants, and iii) to discuss possibilities for plant growth promotion and plant protection for commercial cultivation of medicinal plants. In addition, we also present a case study performed both to analyse the microbiome of three medicinal plants (Matricaria chamomilla L., Calendula officinalis L. and Solanum distichum Schumach. and Thonn.) cultivated on organically managed Egyptian desert farm and to develop biological control strategies. The soil microbiome of the desert ecosystem was comprised of a high abundance of Gram-positive bacteria of prime importance for pathogen suppression under arid soil conditions. For all three plants, we observed a clearly plant-specific selection of the microbes as well as highly specific diazotrophic communities that overall identify plant species as important drivers in structural and functional diversity. Lastly, native Bacillus spec. div. strains were able to promote plant growth and elevate the plants’ flavonoid production. These results underline the numerous links between the plant-associated microbiome and the plant metabolome.